Partial Ordering of Block Matrices in Minkowski Space - Krishnaswamy, D.; Velmurugan, M. (Communications in Mathematics and Applications, 2021)
In this paper, we study the partial orderings of block matrices and the submatrix partial orderings, we also present the results of star orderings in Minkowski space.